1988
DOI: 10.1136/thx.43.5.388
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of walking test results in chronic obstructive airways disease.

Abstract: Thirty six patients with chronic airflow obstruction were studied to examine (1) the reproducibility and order effect of repeated walking tests when performed over consecutive days or consecutive weeks; (2) the correlation between walking distance and spirometric measurements; and (3) the effect of static visual clues on performance. In study 1, where 12 patients performed 12 walks over three consecutive days, five minute walking distance increased by 33% between walks 1 and 12, half of the increase occurring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
1
16

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(114 citation statements)
references
References 21 publications
7
90
1
16
Order By: Relevance
“…12,13 SMWD is also better reproduced than forced expiratory volume in first second (FEV1) in obstructive lung disease. [13][14][15][16] The reference values and equations available for the SMWT for several countries help predict SMWD. [8][9][10] Percent predict of observed value to the calculated value provides a basis of comparison with healthy population.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 SMWD is also better reproduced than forced expiratory volume in first second (FEV1) in obstructive lung disease. [13][14][15][16] The reference values and equations available for the SMWT for several countries help predict SMWD. [8][9][10] Percent predict of observed value to the calculated value provides a basis of comparison with healthy population.…”
Section: Introductionmentioning
confidence: 99%
“…However, to ensure that tests are reproducible, the walked distance in the second test should not be greater than 10% when compared with the first test, otherwise it is necessary to perform a third test for the appropriate reproducibility of the results 9 . In the present study, the two tests carried out in each one of the corridors were reproducible because the difference between the walked distances was lower than the values identified in the literature 4,9,24,25 . The second test performed in both corridors had a better performance, therefore it was chosen for analysis and comparison of the different lengths.…”
Section: Discussionmentioning
confidence: 82%
“…Several studies have demonstrated that this learning effect can be identified through the increase in the walked distance when two or more tests are performed, mostly due to the control of anxiety, recognition of the limits of the test and neuromuscular adaptation to the activity 4,24,25 . However, to ensure that tests are reproducible, the walked distance in the second test should not be greater than 10% when compared with the first test, otherwise it is necessary to perform a third test for the appropriate reproducibility of the results 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Sabe-se que em diversos testes de esforço o efeito aprendizado pode melhorar o rendimento do indiví-duo 2,15,16 , daí a importância da randomização. Apesar de o tempo no TEsc com EV ser menor, não se pode descartar o efeito aprendizado, sendo interessante novos estudos com aplicação de vários TEsc com EV para se esclarecer esse efeito, semelhante ao realizado com o TC6 2,[15][16][17] .…”
Section: Resultsunclassified
“…Apesar de o tempo no TEsc com EV ser menor, não se pode descartar o efeito aprendizado, sendo interessante novos estudos com aplicação de vários TEsc com EV para se esclarecer esse efeito, semelhante ao realizado com o TC6 2,[15][16][17] . Na padronização do TC6, houve preocupação com a utilização do estímulo verbal 2 , motivado por estudos que mostraram que o estímulo verbal pode aumentar a distância percorrida em até 30 metros 3,4 e assegura máxima motivação e performance do indivíduo 2,18,19 .…”
Section: Resultsunclassified